2018
DOI: 10.1016/j.ijrobp.2018.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Oligometastatic Ovarian Cancer: A Step Toward a Drug Holiday

Abstract: SBRT for oligometastatic ovarian cancer showed good local control and a good toxicity profile. It might be an appealing alternative to other invasive local therapies to delay systemic therapy in the case of chemorefractory disease or intolerance to systemic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 33 publications
(45 reference statements)
7
67
1
Order By: Relevance
“…As far as the primary endpoint is concerned, we documented a rate of 65.2% CR of irradiated lesions; despite the limits inherent to the heterogeneity over time of frequency and type of imaging for assessment of clinical response, our finding well matches with data of some OC SBRT series . The 100% rate of CR reported by Trippa et al is likely to be ascribed to the small sample size and/or the inclusion of only lymph node disease, which is recognized as presenting a higher response to SBRT compared with parenchymal lesions . A comprehensive summary of the literature focused on SBRT in ovarian cancer is reported in supplemental online Table 2.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As far as the primary endpoint is concerned, we documented a rate of 65.2% CR of irradiated lesions; despite the limits inherent to the heterogeneity over time of frequency and type of imaging for assessment of clinical response, our finding well matches with data of some OC SBRT series . The 100% rate of CR reported by Trippa et al is likely to be ascribed to the small sample size and/or the inclusion of only lymph node disease, which is recognized as presenting a higher response to SBRT compared with parenchymal lesions . A comprehensive summary of the literature focused on SBRT in ovarian cancer is reported in supplemental online Table 2.…”
Section: Discussionsupporting
confidence: 81%
“…The independent favorable role of younger age and lower tumor volume (PTV) in predicting CR has been already reported by other studies . Conversely, lymph node lesions showed a higher responsiveness compared with parenchymal disease, and this behavior was confirmed in all settings originated from the combinations of variables identified by the multivariate analysis; similar findings have been mentioned in the literature, but these are few , and a comprehensive evaluation of this issue is lacking. In the context of the personalized medicine, further insights on intrinsic biomolecular features of lymph node and parenchymal lesions would be of interest considering that in our series this variable has emerged as the most powerful independent predictor of CR.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this context, radiotherapy can enhance the immune response against EOC and the effects of immunotherapy. Recently, some authors have demonstrated a role of radiotherapy alone in oligometastatic EOC [68][69][70], and some clinical studies are evaluating the efficacy and safety of checkpoints combined with radiotherapy. The most effective radiotherapy dosage and fractionation to obtain the activation of the immune response are still to be defined.…”
Section: Radiotherapy and Immune Checkpoint Inhibitormentioning
confidence: 99%
“…In 69.5% of patients, no acute or late toxicities were observed. 23% of patients experienced acute grade 1 or 2 GI (gastrointestinal) toxicity, 28% of patients experienced grade 1 or 2 GI toxicity, or grade 1 genitourinary toxicity [13].…”
mentioning
confidence: 99%